RITUAL ADAT NGUNDANG DAYAK HALONG : MENANAMKAN KARAKTER BANGSA DAN MELESTARIKAN BUDAYA DAERAH - NFN Hestiyana (Kantor Bahasa Provinsi Gorontalo, 2019)
Ngundang traditional rituals are one cultural heritage of the Dayak Halong people which continues to be maintained and carried out in traditional rituals. In the Dayak Halong indigenous people, there are several traditional rituals: inviting, namely ngundang baharin malem manta, ngundang baharin malem mandruu, ngundang wadian malem manta, ngundang wadian malem mandruu, ngundang palas kapateian, and ngundang palas nimbuk. This study aims to describe the preservation of regional culture in traditional rituals ngundang Dayak Halong as a means of instilling national character. The method used in this study is a qualitative descriptive method. This research data in the form of oral speeches in traditional rituals ngundang. In collecting data techniques used observing, recording, and interviewing. Analyzing is done with understanding, interpretation, and meaning, then they are presented in the form of description. From the results of the study, it is found that the preservation of regional culture in traditional rituals ngundang Dayak Halong as a means of instilling national character through values as follows: (1) religious, (2) honest, (3) tolerance, (4) discipline, (5) love for the homeland, (6) care for the environment, (7) social care, and (8) responsibility. Keywords: ngundang rituals, Dayak Halong, national character, preservingRitual adat ngundang merupakan warisan budaya leluhur masyarakat Dayak Halong yang terus dipelihara dan dilaksanakan dalam setiap ritual. Pada masyarakat adat DayakHalong, terdapat beberapa ritual adat ngundang, yakni ngundang baharin malem manta, ngundang baharin malem mandruu, ngundang wadian malem manta, ngundang wadian malem mandruu, ngundang palas kapateian, dan ngundang palas nimbuk. Penelitian ini bertujuan mendeskripsikan pelestarian budaya daerah dalam ritual adat ngundang Dayak Halong sebagai sarana menanamkan karakter bangsa. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Data penelitian ini berupa tuturan-tuturan lisan dalam tata ritual adat ngundang. Dalam pengumpulan data, digunakan teknik simak, catat, dan cakap. Penganalisisan dilakukan dengan pemahaman, interpretasi, dan pemaknaan, kemudian disajikan dalam bentuk deskripsi. Dari hasil penelitian ditemukan pelestarian budaya daerah dalam ritual adat ngundang Dayak Halong sebagai sarana menanamkan karakter bangsa dilakukan melalui nilai-nilai sebagai berikut: (1) religius, (2) jujur, (3) toleransi, (4) disiplin, (5) cinta tanah air, (6) peduli lingkungan, (7) peduli sosial, dan (8) tanggung jawab. Kata kunci: ritual, ngundang, Dayak Halong, karakter bangsa, pelestarian